Development of an exercise-specific Parkinson’s Disease Questionnaire: the PDQ-exercise - Morley, D; Dummett, S; Kelly, L; Jenkinson, C (Wiley, 2021)
Background: Exercise is now a significant and key component in the management of Parkinson’s disease. However, no self-report, Parkinson’s-specific measure of exercise currently exists.